THE NATURAL BEAUTIES OF RIO PARDINHO – SANTA CRUZ DO SUL – RS - Bräunig, Carin Rosane; Dias, Cíntia Betina Pagel; Silveira, Lisane Sirlei Bock (Seven Editora, 2026)
The project “The Natural Beauties of Rio Pardinho – Santa Cruz do Sul – RS”, developed by the 7th grade classes 71 and 72 of the Christiano João Smidt Municipal Elementary School, linked to the Municipal Department of Education of Santa Cruz do Sul, aimed to investigate, record and disseminate the main natural, historical and cultural points of Rio Pardinho – a district located 10 kilometers from the city, encouraging environmental awareness and the appreciation of local identity. The research was carried out in an interdisciplinary manner, involving the subjects of Geography, Portuguese Language and German Language, integrating theory and practice through bibliographic research, interviews with residents, field visits and textual and artistic productions. Among the sites studied, the following stand out: the Paraíso Pedagogical Site, the Mosteiro da Santíssima Trindade (Monastery of the Holy Trinity), the Casa do Colono (Settler’s House), Cucas Gressler (Gressler’s Cakes), the Lago Dourado Water Intake Dam, the Sítio Thomas Ecke (Thomas Ecke Site), the Igreja Evangélica Imigrante de Rio Pardinho (Immigrant Evangelical Church of Rio Pardinho), and the Cascata do Salto Rio Pardinho-Sinimbu (Rio Pardinho-Sinimbu Waterfall), in addition to rural enterprises and pedagogical spaces in the region. The work culminated in the production of brochures, maps, murals, videos, and narrative, descriptive, and poetic texts, presented at the School’s Work Exhibition by 7th-grade students on November 1st, 2025. As a result, the students expanded their knowledge of the region’s natural and historical heritage, strengthened their sense of belonging, and understood that tourism, culture, and environmental preservation can go hand in hand when supported by education and civic participation.